Cellular V2X communications in the presence of big vehicle shadowing: performance analysis and mitigation - Nguyen, Hieu T. (2023)
In Intelligent Transportation Systems (ITS), vehicular networks are enabling technologies for onboard data services such as traffic safety, user infotainment, etc. Vehicular networks face many challenges when it comes to providing satisfactory quality of service, mainly because of issues that arise from unreliable communication in unfavorable propagation conditions. One prime example is Vehicle-to-Vehicle (V2V) communication in the presence of big vehicles that present obstacles in the communication path of smaller vehicles, where the signal strength decays drastically due to the big vehicle shadowing. As a result, the communication range is shortened, and the safety message dissemination capability is reduced. In this paper, we analyze the impact of big vehicle shadowing on V2V communications, taking into account Cellular Vehicle-to-Everything (C-V2X) networks. A geometric as well as a stochastic approach is employed to analyze the length of shadow regions for conventional cars and big vehicles on the road in different scenarios. This paper analyses the effect of large vehicles shadowing on a V2V communication link as a function of the shadow region length. A beamforming-based signal reception technique is proposed in order to mitigate packet collisions caused by hidden nodes. Considering relaying operation by big vehicles, three relaying schemes are proposed to improve the V2V message dissemination performance. Extensive simulations are conducted to demonstrate the effectiveness of the proposed schemes.